Polyhydroxyalkanoate (PHA): Properties and Modifications - Sharma, Vibhuti; Sehgal, Rutika; Gupta, Reena (Polymer (Guilford), 2021)
There are a wide range of biopolymers produced by a number of different microorganisms. Polyhydroxyalkanoates are also a diverse group among these biopolymers. In recent times, PHA is gaining a lot of attraction due to its properties like biodegradability, biocompatibility, hydrophobicity, etc. but on the other hand, these biopolymers also possess some disadvantages which limit their competition with synthetic polymers. Therefore, to overcome these limitations, PHAs are being modified to improve their properties for their potential applications in different fields. This review comprises different PHA modification methods which include physical bending using natural and synthetic polymers, different approaches of chemical modification and some biological modification methods. The aim of this review is to represent new approaches and ideas to improve the degradable properties of PHAs and to present them as one of the valuable and eco-friendly biopolymer, so that, they can contribute their potentials in various fields. [Display omitted] •Replacement of conventional synthetic plastics with PHA.•PHA possesses properties like biodegradability, renewability, biocompatibility, etc.•Modifications of PHA using physical, chemical and biological methods for their efficient production.